The Teacher Development: The Case Study of A Local Polytechnic Vocational College - Long, Dang The (VNU Journal of Science: Education Research, 2022)
Technical and Vocational Education and Training (TVET) plays a crucial role in the structure and philosophy of Vietnam’s education, contributing significantly to the training of human resources with practical knowledge and technical skills, which well aligns with the policy orientation of the national economic development. After having transferred the governance to the Ministry of Labour, Invalids and Social Affairs, TVET now has a relatively solid legal frameworks and initial stable development. However, the quality of TVET teachers is still not as high as expected. This study, through a case study, with both qualitative and quantitative methods, argues that although sufficient in quantity, TVET teachers are is still weak in quality. Most teachers meet both professional qualifications and additional requirements in English ​​and Information Technology, but their ability to use and apply these skills in the teaching is limited. The survey also shows that TVET institutions are doing a better job of managing teachers than attracting and providing necessary professional development for their teachers.